Determination of Groundwater Recharge Area by Using Hydroisotope Technic of Sei Bingei Area and Surrounding Areas, Langkat Regency, North Sumatra - Azmin Nuha; Heru Hendrayana; Agus Budhie Wiyatna; Doni Prakasa Eka Putra; Azwar Satry Muhammad (Geological Engineering Department Universitas Gadjah Mada, 2020)
Determination of Groundwater Recharge Area by Using Hydroisotope Technic of Sei Bingei Area and Surrounding Areas, Langkat Regency, North Sumatra